(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2026)
The intestinal microbiota plays a crucial role in the maturation of the immune system and gastrointestinal function in newborns, particularly in premature infants. In the early neonatal period, preterm infants are highly vulnerable to gastrointestinal enteropathy due to immaturity of the intestinal barrier, altered microbial colonization, and exposure to intensive medical interventions. This study explores the features of intestinal microbiota composition in premature infants diagnosed with gastrointestinal enteropathy during the early neonatal period. Special attention is given to the imbalance between beneficial and opportunistic microorganisms, reduced microbial diversity, and the predominance of pathogenic bacteria. In the context of Uzbekistan, where the prevalence of premature births remains a significant public health concern, understanding microbiota-related mechanisms is essential for improving neonatal outcomes. The findings highlight the importance of early microbiota modulation strategies, including breastfeeding support and probiotic use, to prevent severe gastrointestinal complications in premature infants.